THE ROLE OF p53 AND CASPASE IN REGULATION APOPTOSIS ACTIVITY - Afrisusnawati Rauf (Universitas Islam Negeri Alauddin Makassar, 2013)
Apoptosis, or programmed cell death, is a common property of all multicellular organism. Apoptosis occurs normally during development and aging and as a homeostatic mechanism to maintain cell populations in tissue. Apoptosis also accurs as a defense mechanism such as in immune reactions or when cells are damaged by disease or noxious agents. Dysregulation of apoptosis leads to a variety of human pathologies including cancer, autoimmune disease, and neurodegenerative disorders.